Editorial - Zeta de Pozo, Rosa (2018)
We present this new edition with the pleasant new  that  our journal has been accepted for inclusion in SCOPUS. We observe that researchers feel some concern for the innovative elements in the world of communication, but also for the universal communication themes as it is seen at all times. Innovative trends, with technological roots, must be known, and adopted to the extent that they contribute to the improvement of all actors of communication and ultimately of the whole society. And in that digital environment, we notice the presence of universal issues. Transmedia storytelling of TV series and at the same time how power or cultural identities are reflected in them, brings our attention. Fashion films are explored, as new advertising formats, and the gender vision that is transmitted in the messages expresses great concern.